RANCANG BANGUN SISTEM KONTROL PEMUTAR ANTENA YAGI BERBASIS MIKROKONTROLER DALAM MENGATUR ARAH PENERIMAAN SINYAL TELEVISI - Yusuf, Mohammad; Kerta Putrawan, I Kadek Aditya; Pramaita, Nyoman; Djuni Hartawan, I Gusti Agung Diafari; Putu Raka Agung, I Gusti Agung; Oka Widyantara, I Made (Jurnal SPEKTRUM; Vol 11 No 4 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i04.p1, 2024)
Television generally requires an antenna to capture. The commonly used is the Yagi antenna. This type of antenna needs to be rotated to adjust the direction of signal reception to improve image and sound quality. In this design, users simply need to press a button integrated into two systems: a wireless system for remote control and a push-button system for close-range control. These systems adjust the antenna's position to the right or left, according to the direction of the desired signal. The push-button system features five push buttons as inputs, which respond to pre-programmed commands, and the wireless system requires pin initialization connected to the ESP32, which links to the Blynk application and the Internet. Blynk displays the current angle sensor measurements uploaded to the database by the ESP32. Testing of the push-button control system showed a consistent match between the antenna mast's angle rotation on the LCD display and the physical degree arc, with an average error rate of 0.74%. Testing of the wireless control system using the Blynk application with IoT concepts also demonstrated consistency between the test results of the wireless control circuit and the antenna mast's angle rotation, with an average error rate of 0.73%.